T cells expressing multiple co‐inhibitory molecules in acute malaria are not exhausted but exert a suppressive function in mice. Issue 2 (25th November 2021) - Brandi, Johannes; Lehmann, Cari; Kaminski, Lea‐Christina; Schulze zur Wiesch, Julian; Addo, Marylyn; Ramharter, Michael; Mackroth, Maria; Jacobs, Thomas; Riehn, Mathias
Abstract: Overwhelming activation of T cells in acute malaria is associated with severe outcomes. Thus, counter‐regulation by anti‐inflammatory mechanisms is indispensable for an optimal resolution of disease. Using Plasmodium berghei ANKA (PbA) infection of C57BL/6 mice, we performed a comprehensive analysis of co‐inhibitory molecules expressed on CD4 + and CD8 + T cells using an unbiased cluster analysis approach. We identified similar T cell clusters co‐expressing several co‐inhibitory molecules like programmed cell death protein 1 (PD‐1) and lymphocyte activation gene 3 (LAG‐3) in the CD4 + and the CD8 + T cell compartment. Interestingly, despite expressing co‐inhibitory molecules, which are associated with T cell exhaustion in chronic settings, these T cells were more functional compared to activated T cells that were negative for co‐inhibitory molecules. However, T cells expressing high levels of PD‐1 and LAG‐3 also conferred suppressive capacity and thus resembled type I regulatory T cells. To our knowledge, this is the first description of malaria‐induced CD8 + T cells with suppressive capacity. Importantly, we found an induction of T cells with a similar co‐inhibitory rich phenotype in Plasmodium falciparum ‐infected patients. In conclusion, we demonstrate that malaria‐induced T cells expressing co‐inhibitory molecules are not exhausted, but acquire additional suppressive capacity, which might represent an immune regulatory pathway to prevent further activation of T cells during acute malaria. Abstract : In Malaria, caused by Plasmodium infection, the blood stage but not the liver stage induces subsets of effector T cells, including cytotoxic CD8 + T cells, expressing various co‐inhibitory receptors like LAG‐3 or PD‐1. Strikingly, these T cells are not exhausted but show suppressive capacity, despite their effector function.